Anti-Influenza Virus Activity and Chemical Components from the Parasitic Plant Cuscuta japonica Choisy on Dimocarpus longans Lour - Cheng, Ju-Chien; Liaw, Chia-Ching; Lin, Ming-Kuem; Chen, Chao-Jung; Chao, Chien-Liang; Chao, Chih-Hua; Kuo, Yueh-Hsiung; Chiu, Yen-Po; Peng, Yu-Shin; Huang, Hui-Chi (Molecules (Basel, Switzerland), 2020)
Dodder (Cuscuta spp.) is a parasitic weed damaging many plants and agricultural production. The native obligate parasite Cuscuta japonica Choisy (Japanese dodder) parasitizes Dimocarpus longans Lour., Ficus septica Burm. F., Ficus microcarpa L.f., Mikania micrantha H.B.K. and Melia azedarach Linn, respectively. Five Japanese dodders growing on different plants exhibit slightly different metabolites and amounts which present different pharmacological effects. Among these plants, a significant antiviral activity against influenza A virus (IAV) was found in Japanese dodder parasitizing on D. longans Lour. (CL). To further explore methanol extract components in Japanese dodder (CL), four undescribed aromatic glycosides, cuscutasides A–D (compounds 1–4) were isolated, together with twenty-six known compounds 5–30. The chemical structures of 1–4 were elucidated using a combination of spectroscopic techniques. The eighteen isolated compounds were evaluated for antiviral activity against IAV activity. Among them, 1-monopalmitin (29) displayed potent activity against influenza A virus (A/WSN/1933(H1N1)) with EC50 2.28 ± 0.04 μM and without noteworthy cytotoxicity in MDCK cells. The interrupt step of 29 on the IAV life cycle was determined. These data provide invaluable information for new applications for this otherwise harmful weed.